Alien species and climate change drive shifts in a riverine fish community and trait compositions over 35 years - Le Hen, Gwendaline; Balzani, Paride; Haase, Peter; Kouba, Antonín; Liu, Chunlong; Nagelkerke, Leopold A J; Theissen, Nikola; Renault, David; Soto, Ismael; Haubrock, Phillip J (The Science of the total environment, 2023)
Alien fish substantially impact aquatic communities. However, their effects on trait composition remain poorly understood, especially at large spatiotemporal scales. Here, we used long-term biomonitoring data (1984-2018) from 31 fish communities of the Rhine river in Germany to investigate compositional and functional changes over time. Average total community richness increased by 49 %: it was stable until 2004, then declined until 2010, before increasing until 2018. Average abundance decreased by 9 %. Starting from 198 individuals/m2 in 1984 abundance largely declined to 23 individuals/m2 in 2010 (-88 %), and then consequently increased by 678 % up to 180 individuals/m2 until 2018. Increases in abundance and richness starting around 2010 were mainly driven by the establishment of alien species: while alien species represented 5 % of all species and 0.1 % of total individuals in 1993, it increased to 30 % (7 species) and 32 % of individuals in 2018. Concomitant to the increase in alien species, average native species richness and abundance declined by 26 % and 50 % respectively. We identified increases in temperature, precipitation, abundance and richness of alien fish driving compositional changes after 2010. To get more insights on the impacts of alien species on fish communities, we used 12 biological and 13 ecological traits to compute four trait metrics each. Ecological trait dispersion increased before 2010, probably due to diminishing ecologically similar native species. No changes in trait metrics were measured after 2010, albeit relative shares of expressed trait modalities significantly changing. The observed shift in trait modalities suggested the introduction of new species carrying similar and novel trait modalities. Our results revealed significant changes in taxonomic and trait compositions following alien fish introductions and climatic change. To conclude, our analyses show taxonomic and functional changes in the Rhine river over 35 years, likely indicative of future changes in ecosystem services.
Keywords: Traits; Alien species; ryby; Ecosystem; řeky; Functional ecology; Freshwater fish; zvířata; Germany; klimatické změny; Německo; Rivers; Fishes; Climate Change; biodiverzita; Rhine river; zavlečené druhy; Long-term study; Animals; Introduced Species; ekosystém; Biodiversity